Proximity Based Authentication in IoT - Neupane, Suraj (fi=Turun yliopisto|en=University of Turku|, 2015)
IoT consists of essentially thousands of tiny sensor nodes interconnected to the internet, each one of which executes the programmed functions under memory and power limita- tions. The sensor nodes are distributed mainly for gathering data in various situations. IoT envisions the future technologies such as e-health, smart city, auto-mobiles automa- tion, construction sites automation, and smart home. Secure communication of data under memory and energy constraints is major challenge in IoT. Authentication is the first and important phase of secure communication. This study presents a protocol to authenticate resource constraint devices in physical proximity by solely using the shared wireless communication interfaces. This model of authentication only relies on the abundance of ambient radio signals to authenticate in less than a second. To evaluate the designed protocol, SkyMotes are emulated in a network environment simulated by Contiki/COOJA. Results presented during this study proves that this approach is immune against passive and active attacks. An adversary located as near as two meters can be identified in less than a second with minimal expense of energy. Since, only radio device is used as required hardware for the authentication, this technique is scalable and interoperable to heterogeneous nature of IoT.